DETERMINATION OF KINETIC PARAMETERS AND THE EFFECT OF ION MG2+ INHIBITION INTO PECTINASE ACTIVITIES. - Anggraini, Dian Puspita; Sulistiana, Devita; Agustina, Dwi Kameluh; Ulimaz, Almira (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2020)
The purpose of study was to determine kinetic parameters and inhibitory effect of Mg2+ ions on pectinase. Activity test performed at pH 4,5 temperature 55oC for 50' with 10 mm concentrations of each ion 0-10mm. Galacturonic acid content, as product of pectin substrate hydrolysis, was used as basis for determining activity and analyzed by visible spectrophotometry. At concentrations 2 and 4 mm Mg2+ act as an activator, but at concentrations 6, 8, and 10 mM as inhibitors. The value of KM with and without inhibitors is almost same, that is 0.3145% and 0.3105% but value of Vm from both are different, that is 80,645 ?g.ml-1.minute-1 and 62,112 ?g.ml-1.minute-1. The conclusion that type of inhibitory pectinase with Mg2+ is a non-competitive inhibition. The inhibition constant value (Ki) is 26,84.